Era Tabla d’eths Tros Rouyes vs. el Archivo de la Junta General del Valle de Roncal y la Sentencia Arbitral del Tributo de las Tres Vacas guardada en los Archivos Departamentales de los Pirineos Atlánticos - Lopez-Mugartza Iriarte, Juan Karlos (Huarte de San Juan. Filología y Didáctica de la Lengua, 2014)
This paper studies the ancient names of the mountain now known as La Mesa de los Tres Reyes (the place where Navarre, Aragon and Bearne are joined) that appear in different documents from the archives of the General Board of the Roncal Valley and the Departmental Archives of the Atlantic Pyrenees. Based on these documents, the assumed Gascon name of the mountain must be critically debated. This study is mostly based on the Arbitrary Judgment of 1375 which establishes to the people of Baretous valley the obligation of give yearly three cows of two years old to the people of the Roncal valley. That document is written in French and is saved in the Departmental Archives of the Atlantic Pyrenees in Pau (France). This article examines the names of persons and places contained over there. Attached to the main document, there are other documents saved in the same place. One of them highlights which is written in Gascon-Béarn, and gives news of the destruction of the original judgment during the burning of the municipal archives of Isaba of the XV century.